Programmed Death Ligand 1 (PD-L1) Expression in Lung Adenocarcinoma Patients - Rahmat Hidayat; Noni Novisari Soeroso; Elisna Syahruddin; Dian Cahyadi; Setiaputra Setiaputra (Indonesian Society of Respirology (ISR), 2021)
Background: Programmed Death Ligand 1 (PD-L1) is a protein found in tumor cells that could inactivate T-cells. This research was done to identify the characteristics of lung adenocarcinoma patients to PD-L1 expression in Medan. Method: Descriptive research with a cross-sectional design was used and the study was done for 12 months (January – December 2018). Sample’s collection was done at RSUP (Central Public Hospital) H. Adam Malik and the samples diagnosed with lung adenocarcinoma based on histopathological subtyping were sent to the laboratory of Dharmais Jakarta Hospital where the Ventana 22C3 Immunohistochemistry Staining was done. Results: Staining was done in 52 samples at Dharmais Jakarta Hospital and only 35 samples were deemed acceptable. In this study, participants’ ages ranged from 40 to 60 years, where the majority were male patients, 31 (88.6%) and 33 patients (82.5%) were at an advanced stage (III and IV). Conclusion: The study found that the PD-L1 expression was mostly observed in male at the age range of 40 – 60 years and stage IV lung adenocarcinoma patients with Tumour Proportion Score (TPS) of 1 – 49%.